Conspiracy of silence: cultural conflict as a risk factor for the development of eating disorders among second-generation Canadian South Asian women. Issue 1 (2nd January 2017) - Mustafa, Nida; Zaidi, Arshia U.; Weaver, Robert R.
ABSTRACT: This phenomenological study examines second-generation Canadian South Asian women's experiences of an eating disorder, and explores issues of culture conflict in relation to mental health tensions and body/self-concept distortions. Eight second-generation South Asian women who have sought help for an eating disorder participated in semi-structured interviews. Using feminist and transcultural theories, our analyses suggest that body image distortions stem from myriad pressures women face in relation to others in their lives. In constant attempt to follow familial and cultural expectations, these women felt a disconnection and alienation linking to mental pressure, which may be a factor in the development of self-dissatisfaction and ultimately eating disorders for this group. This research elevates awareness of eating disorders within the South Asian community as a way to break the 'conspiracy of silence' that surrounds this growing health concern.